The outbreak of the covid-19 pandemic in Malaysia: a Conceptual analysis - Alesia Sigang Gugkang; Yee-Ee Chia; Lilian Shiau-Gee Lee (UMS, 2022)
Leading to declining business activity, disrupted industrial supply chains, and employee quarantine, the COVID-19 outbreak not only raised health concerns but also had a significant economic impact on Malaysia. The objective of this conceptual paper is to discuss the overall impact of the COVID-19 pandemic on Malaysia's most vulnerable populations. This study proposes quantitative research approach based on statistical data to further explore our objectives. From 4th May 2020 to 30th April 2021, the key data on the total number of confirmed cases of COVID-19 and the total number of individual recovered cases were collected via the Ministry of Health Malaysia. This study concludes that recovery and stabilization measures are necessary in times of pandemic, where economic sectors have been allowed to open up under strict guidelines. Thus, the economy could be resurrected to meet today’s issues by implementing standard operating procedures (SOPs), stimulating investment and businesses, and restoring the economy in stages.